Safety and Preliminary Efficacy of Lorcaserin for Cocaine Use Disorder: A Phase I Randomized Clinical Trial - Johns, Sade E.; Keyser-Marcus, Lori; Abbate, Antonio; Boone, Edward; Van Tassell, Benjamin; Cunningham, Kathryn A.; Anastasio, Noelle C.; Poklis, Justin L.; Ramey, Tatiana; Moeller, F. Gerard (Frontiers in Psychiatry, 2021)
Background and Objectives: Preclinical studies show serotonin (5-HT) 5-HT2C receptor (5-HT2CR) agonists reduce cocaine-seeking and cocaine intake. This study examined safety of the 5-HT2CR agonist lorcaserin administered with cocaine in participants with cocaine use disorder (CocUD). Secondarily, subjective response to cocaine and choice of cocaine vs. money were examined. Methods: A double-blind, randomized, placebo-controlled trial of 25 inpatient non-treatment seeking participants with CocUD. Participants were randomized to either lorcaserin (n = 17) or placebo (n = 8). Primary outcome measures included cardiovascular measures and plasma cocaine levels. Secondary measures of subjective response to cocaine were assessed using a visual analog scale (VAS) and cocaine vs. money progressive ratio choice sessions. Results: Thirteen randomized participants were included in the final analysis. No serious or unexpected adverse events were related to lorcaserin. There were no significant interactions between cocaine and lorcaserin on cardiovascular measures, plasma cocaine, or subjective ratings. After multiple comparisons correction, cocaine significantly increased blood pressure, heart rate, and QTc. Lorcaserin significantly decreased VAS ratings of “feel irritable”, “feel hungry” and “I am craving”. For the cocaine vs. money choice procedure, there was a significant interaction between choice (cocaine vs. money) and lorcaserin. Participants treated with lorcaserin were more likely to choose cocaine. Discussion and Conclusions: This study showed safety of lorcaserin administered with cocaine but lack of efficacy to reduce the reinforcing effects of cocaine. Scientific Significance: This study is the first to show a disconnect between effects of 5-HT2CR agonists on craving and cocaine choice in human cocaine users.